Cervical Cancer, Papillomavirus, and miRNA Dysfunction - Bañuelos-Villegas, Evelyn Gabriela; Pérez-yPérez, María Fernanda; Alvarez-Salas, Luis Marat (Frontiers in Molecular Biosciences, 2021)
Cervical cancer is the leading cause of death by cancer in women from developing countries. The main risk factor for the development of cervical cancer is persistent infection with human papilloma virus (HPV) HPV16 and HPV18. Nevertheless, only a few women with a morphologic expression of HPV infection progress into invasive disease suggesting the involvement of other factors in cervical carcinogenesis. MicroRNAs (miRNAs) are highly conserved small non-coding RNAs that negatively regulate the expression of coding genes including those involved in fundamental biological processes and human cancer. Deregulation of miRNAs has been widely reported in cervical cancer. This work focuses on reviewing the miRNAs affected during the HPV infection process, as well relevant miRNAs that contribute to the development and maintenance of the malignancy of cervical cancer cells. Finally, we will recapitulate miRNAs that show the ability to distinguish between healthy patients or those with precancerous lesions from patients with cervical tumors.